Coronavirus disease 2019 outbreak: Strengthening infection prevention and control measures to reduce hospital-acquired infection - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Apollo Medicine)
The coronavirus disease-2019 (COVID-19) outbreak has been declared a public health emergency of international concern and now the overall risk of transmission at global level has also been decided as very high based on the available facts. The effective containment of the infection will require a coordinated response from multiple stakeholders and strengthening of infection prevention and control (IPC), surveillance, diagnostics, treatment, risk communication, and research activities. Among all, it will be ideal to give more emphasis toward IPC as it is a major domain in prevention and mitigation of the ongoing outbreak. It is quite obvious that giving only attention to personal protective equipment will not accomplish significant gains unless it is well supported by administrative, environmental, and engineering interventions. In conclusion, in the battle against the COVID-19, the IPC measures need to be strengthened extensively both in hospital and community settings and thus specific attention has to be given toward the same.